Malnutrition and sarcopenia predict post‐liver transplantation outcomes independently of the Model for End‐stage Liver Disease score. Issue 1 (1st February 2016) - Kalafateli, Maria; Mantzoukis, Konstantinos; Choi Yau, Yan; Mohammad, Ali O.; Arora, Simran; Rodrigues, Susana; de Vos, Marie; Papadimitriou, Kassiani; Thorburn, Douglas; O'Beirne, James; Patch, David; Pinzani, Massimo; et al.
Abstract: Background: Although malnutrition and sarcopenia are prevalent in cirrhosis, their impact on outcomes following liver transplantation is not well documented. Methods: The associations of nutritional status and sarcopenia with post‐transplant infections, requirement for mechanical ventilation, intensive care (ICU) and hospital stay, and 1 year mortality were assessed in 232 consecutive transplant recipients. Nutritional status and sarcopenia were assessed using the Royal Free Hospital‐Global Assessment (RFH‐GA) tool and the L3‐psoas muscle index (L3‐PMI) on CT, respectively. Results: A wide range of RFH‐SGA and L3‐PMI were observed within similar Model for End‐stage Liver Disease (MELD) sub‐categories. Malnutrition and sarcopenia were independent predictors of all outcomes. Post‐transplant infections were associated with MELD (OR = 1.055, 95%CI = 1.002–1.11) and severe malnutrition (OR = 6.55, 95%CI = 1.99–21.5); ventilation > 24 h with MELD (OR = 1.1, 95%CI = 1.036–1.168), severe malnutrition (OR = 8.5, 95%CI = 1.48–48.87) and suboptimal donor liver (OR = 2.326, 95%CI = 1.056–5.12); ICU stay > 5 days, with age (OR = 1.054, 95%CI = 1.004–1.106), MELD (OR = 1.137, 95%CI = 1.057–1.223) and severe malnutrition (OR = 7.46, 95%CI = 1.57–35.43); hospital stay > 20 days with male sex (OR = 2.107, 95%CI = 1.004–4.419) and L3‐PMI (OR = 0.996, 95%CI = 0.994–0.999); 1 year mortality with L3‐PMI (OR = 0.996, 95%CI = 0.992–0.999). Patients at the lowest L3‐PMI receiving suboptimal grafts had longer ICU/hospital stay and higher incidence of infections. Conclusions: Malnutrition and sarcopenia are associated with early post‐liver transplant morbidity/mortality. Allocation indices do not include nutritional status and may jeopardize outcomes in nutritionally compromised individuals.